(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The use of innovative techniques and technologies is required to find a practical solution to problems in the socio-economic and educational spheres on a global scale. In the article of students’ technical creativity in formation done increase in the eye caught works, modern lesson transition stages, innovative from technologies lesson in the process use methods analysis done. Analytical data robotics basics direction based on light up given.